Sustainability Appeals and Gen Z’s Willingness to Pay in Hostels: The Role of Gender and Culture - Rai, Anjila; Matikkala, Teemu (My University, 2025)
Sustainability is a burning issue in the global tourism and hospitality industry, causing a shift in business strategies as well as consumer choices. Multiple studies have examined sustainability aspects in hotels, but very little attention has been directed towards hostels, which have emerged as a popular accommodation option. This study focuses on Generation Z and how they view the sustainability appeals in the context of hostels, an accommodation sector that particularly targets young and economically aware travelers. The objective of this research is to find out which sustainability appeal (environmental, social/community, or eco-nomic) has the greatest impact on Generation Z travelers’ willingness to pay (WTP) and to investigate the moderating effects of gender and cultural values on these relationships. This study is based on the theoretical framework of the Triple Bottom Line, the Theory of Planned Behaviour, and Hofstede’s cultural dimensions. A quantitative research method was implemented, and scenario-based survey data from 66 respondents were collected. Each scenario had a clear focus on one sustainability appeal, while respondents were asked how important the appeal was to them, along with their Willingness to pay (WTP) with a monetary amount provided in Euros. Along with the analysis of the WTP for different sustainability appeals, comparisons were made between respondents’ different cultures based on the established cultural theoretical framework of Hofstede’s. Similarly, gender differences were analyzed. The results provided a valuable contribution to understanding sustainability appeals effect size. Moreover, different factors were tested. Some results were contradictory to the ex-pected findings based on the literature review. Mainly, the surprising insight was that eco-nomic appeals were deemed the most important and had the highest WTP. However, those from collectivist cultures were found to have a stronger relationship with the social sustainability appeals, as was expected. Females were also found to have a higher WTP for economic sustainability compared to males. These findings can be applied by hostel managers to un-derstand what kind of sustainable marketing appeal would be the most effective for different groups, mainly based on gender and cultural orientation. With these findings used for more effective targeted marketing, a hostel can stand out from its competitors.
Keywords: fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business